Relentless [compact disc] - Greenwood, Jonny (Parlophone, 2023)
The Pretenders return with their fourteenth studio album. Arriving with the impulsiveness and attitude that at once defines the band's eternal spirit, the album is a clearly defined snapshot of where the Pretenders are in 2023.